Squamous Cell Carcinoma within a Congenital Nevus Sebaceous: Case Report and Literature Review - Petchlada Achavanuntakul; Kanchalit Thanomkitti (Karger Publishers, 2021)
Nevus sebaceous (NS) is a benign hamartoma that typically occurs on the head and neck area at birth. Occasionally, secondary neoplasms can develop on top of the original nevus, which usually occur in the middle age. Squamous cell carcinoma (SCC) arising in NS may occur but is very rare. We report the case of a 44-year-old female with an asymptomatic erythematous papule arising within a hairless yellowish plaque on the left parietal area of her scalp for a month. An excisional biopsy was done, and the histopathologic examination revealed SCC arising in the NS.